Polycomb group gene Ezh2 regulates mammary gland morphogenesis and maintains the luminal progenitor pool - Michalak, Ewa Malgorzata; Nacerddine, Karim; Pietersen, Alexandra; Beuger, Vincent; Pawlitzky, Inka; Cornelissen‐Steijger, Paulien; Wientjens, Ellen; Tanger, Ellen; Seibler, Jost; van Lohuizen, Maarten; Jonkers, Jos (Stem cells (Dayton, Ohio), 2013)
ABSTRACT Specification of the cellular hierarchy in the mammary gland involves complex signaling that remains poorly defined. Polycomb group proteins are known to contribute to the maintenance of stem cell identity through epigenetic modifications, leading to stable alterations in gene expression. The polycomb protein family member EZH2 is known to be important for stem cell maintenance in multiple tissues, but its role in mammary gland development and differentiation remains unknown. Our analyses show that EZH2 is predominantly expressed in luminal cells of the mouse mammary epithelium. As mammary gland development occurs mostly after birth, the analysis of EZH2 gene function in postnatal development is precluded by embryonic lethality of conventional EZH2 knockout mice. To investigate the role of EZH2 in normal mammary gland epithelium, we have generated novel transgenic mice that express doxycycline‐regulatable short hairpin (sh) RNAs directed against Ezh2. Knockdown of EZH2 results in delayed outgrowth of the mammary epithelium during puberty, due to impaired terminal end bud formation and ductal elongation. Furthermore, our results demonstrate that EZH2 is required to maintain the luminal cell pool and may limit differentiation of luminal progenitors into CD61+ differentiated luminal cells, suggesting a role for EZH2 in mammary luminal cell fate determination. Consistent with this, EZH2 knockdown reduced lobuloalveolar expansion during pregnancy, suggesting EZH2 is required for the differentiation of luminal progenitors to alveolar cells.Stem Cells 2013;31:1910‐1920